EQ-5D studies in musculoskeletal and connective tissue diseases in eight Central and Eastern European countries: a systematic literature review and meta-analysis - Zrubka, Zsombor; Rencz, Fanni; Závada, Jakub; Golicki, Dominik; Rupel, Valentina Prevolnik; Simon, Judit; Brodszky, Valentin; Baji, Petra; Petrova, Guenka; Rotar, Alexandru; Gulácsi, László; Péntek, Márta (Rheumatology international, 2017)
EQ-5D is becoming the preferred instrument to measure health-state utilities involved in health technology assessment. The objective of this study is to assess the state of EQ-5D research in musculoskeletal disorders in 8 Central and Eastern European countries and to provide a meta-analysis of EQ-5D index scores. Original research articles published in any language between Jan 2000 and Sept 2016 were included, if they reported any EQ-5D outcome from at least two musculoskeletal patients from Austria, Bulgaria, the Czech Republic, Hungary, Poland, Romania, Slovakia, or Slovenia. Risk of bias was assessed with the Cochrane Collaboration's tool. Twenty-nine articles (5992 patients) were included on rheumatoid arthritis (n = 7), osteoporosis (n = 5), chronic pain (n = 5), osteoarthritis (n = 4), ankylosing spondylitis (n = 2), psoriatic arthritis (n = 2), total hip replacement (n = 2), and scleroderma (n = 2). Low back pain was under-represented, while studies in neck pain, systemic lupus erythematosus, gout, and childhood disorders were lacking. EQ-5D index scores were reported in 24 studies, while the version of the instrument and the value-set was not specified in 41% and 46% of the articles, respectively. Meta-analysis was performed on 24 disease states involving 6876 observation points. Intervention effect was reported in 22 subgroups, out of which risk of bias was low in 41%. This review provides recommendations to improve reporting standards of EQ-5D results and highlights potential areas for future research. Coordinated research in conditions with greatest public health impact as well as a development of a regional value-set could provide locally relevant health-state utilities that are transferable among countries within the region.
Keywords: Randomized Controlled Trials as Topic; Musculoskeletal Diseases; Musculoskeletal diseases; Qualitative Research; zdravotnické přehledy; Quality-Adjusted Life Years; Europe; Female; ženské pohlaví; průřezové studie; kvalitativně upravené roky života; kvalita života; Health Status; lidé; zdravotní stav; Evropa; Meta-analysis; EQ-5D; nemoci pojiva; Patient reported outcomes; retrospektivní studie; Central and Eastern Europe; prospektivní studie; Cross-Sectional Studies; muskuloskeletální nemoci; Male; Prospective Studies; randomizované kontrolované studie jako téma; chronická bolest; Connective Tissue Diseases; Chronic Pain; Health Surveys; mužské pohlaví; Retrospective Studies; Quality of Life; Health-related quality of life; kvalitativní výzkum; Humans